Individual welfare gains from deferred life-annuities under stochastic Lee-Carter mortality - Thomas Post (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2009)
A deferred annuity typically includes an option-like right for the policyholder. At the end of the deferment period, he may either choose to receive annuity payouts, calculated based on a mortality table agreed to at contract inception, or receive the accumulated capital as a lump sum. Considering stochastic mortality improvements, such an option could be of substantial value. Whenever mortality improves less than originally expected, the policyholder will choose the lump sum and buy an annuity on the market granting him a better price. If, however, mortality improves more than expected, the policyholder will choose to retain the deferred annuity. We use a realistically calibrated life-cycle consumption/saving/asset allocation model and calculate the welfare gains of deferred annuities under stochastic Lee- Carter mortality. Our results are relevant both for individual retirement planning and for policymakers, especially if legislation makes annuitization, at least in part, mandatory. Our results also indicate the maximal willingness to pay for the mortality option inherent in deferred annuities, which is of relevance to insurance pricing.
Keywords: D14; D81; D91; G11; G22; J11; J26; 330; Stochastic Mortality; Deferred Annuitization; Retirement Decisions; Annuity Puzzle; Intertemporal Utility Maximization; Lebensversicherung; Private Rentenversicherung; Sterblichkeit; Versicherungstechnisches Risiko; Stochastischer Prozess; Altersgrenze; Zeitpräferenz; Wohlfahrtseffekt; Theorie